Derivación de valores económicos de la producción de leche de bovinos en la parroquia Juan Montalvo utilizando funciones de beneficio. - Mora Echeverría, Mauricio Esteban (2022)
The lack of a genetic improvement program for dairy cattle in the Juan Montalvo parish, Cotopaxi province, has caused the selection of breeders to be carried out without any specific objective, this together with other factors have caused dairy production in general be inefficient. The animals in this sector are mostly racial mixtures born on the farms themselves; It should be noted that the cows show values ​​negative to the adequate ones, thus: an estimated weight gain of -0.25 gr / day, a milk density of 26 g/ml compared to the 28 g/ml suggested in the literature, in addition to a milk production from 5 to 10 liters/day, which is lower than expected under these environmental conditions. According to the data from the INEC agricultural survey in 2019, it is estimated that 4 liters of milk are produced per hectare per day, which translates into limited sustainability of this production, especially in small and medium-sized producers. In the parish there is an average production of 16,320 liters of milk, the average sale price per liter according to the producers is 0.36 cents, however, the real production cost is 0.24 cents, a relatively high cost that can be drastically decreased with better management and genetics. Therefore, the genetic improvement program in dairy cattle was implemented in the first phase, in which the largest number of partners was collected to derive data of productive and economic importance that helped to study the production costs and profitability of the cattle. producers. Based on the information obtained, the main objectives of genetic selection were identified, considering the deficiencies found, which, through the dissemination of the selected genetics, and using reproductive biotechnologies, we hope to improve. The expected contribution of the program is to carry out the first genetic evaluation of cattle in the country and select individuals based on breeding value. The program will have a long-term impact on the economy and on the quality of life of primary milk producers in the sectors involved, by improving efficiency on farms and thus avoiding unfavorable results.